Functionalization of Conflict of Interest Construction in the Context of Corporate Governance of the JSC - Makharoblishvili, Giorgi (Journal of Law, 2022)
The article analyzes the core of the corporate law, the main vector of the principal dilemma of corporate governance, which leads to a conflict of interests and obligations. The specific purpose of corporate law is to create a controlled legal area of conflict of interest between members of an affiliated corporate community or those associated with it. Preventing imbalances between entities with incompatible interests is a systemic part of corporate governance and is called the “owner-proprietor” problem. The separation of ownership and control creates a conflict between rights, duties and interests. A conflict of interest is a potentially feasible threat that implies the possibility of giving an unlawful, personal motive advantage to one party to the transaction at the expense of the other party to the transaction. In corporate law, a potential risk is "translated" as the risk of investing or invested capital, and the risk is "the probability of losing something, expressed as a percentage". The economic consequence of an unlawful advantage is the acquisition of material, financial or other benefits. The construction of a conflict of interest will be transformed into a corporate defense strategy in the context of a normatively regulated nature. The use of its content as a corporate strategy guarantees the purposeful functioning of the JSC, and in the event of a dispute, it enables the court to correctly determine the orientation of the judicial analysis. As a result, the regulatory structure of the conflict of interest at the legislative level creates a JSC-controlled buffer of conflict of interest.